Hot and bothered: Using trait-based approaches to assess climate change vulnerability in reptiles. (December 2016) - Böhm, Monika; Cook, Daniel; Ma, Heidi; Davidson, Ana D.; García, Andrés; Tapley, Benjamin; Pearce-Kelly, Paul; Carr, Jamie
Abstract: One-fifth of the world's reptiles are currently estimated as threatened with extinction, primarily due to the immediate threats of habitat loss and overexploitation. Climate change presents an emerging slow-acting threat. However, few IUCN Red List assessments for reptiles explicitly consider the potential role of climate change as a threat. Thus, climate change vulnerability assessments can complement existing Red List assessments and highlight further, emerging priorities for conservation action. Here we present the first trait-based global climate change vulnerability assessment for reptiles to estimate the climate change vulnerability of a random representative sample of 1498 species of reptiles. We collected species-specific traits relating to three dimensions of climate change, sensitivity, low adaptability, and exposure, which we combined to assess overall vulnerability. We found 80.5% of species highly sensitive to climate change, primarily due to habitat specialisation, while 48% had low adaptability and 58% had high exposure. Overall, 22% of species assessed were highly vulnerable to climate change. Hotspots of climate change vulnerability did not always overlap with hotspots of threatened species richness, with most of the vulnerable species found in northwestern South America, southwestern USA, Sri Lanka, the Himalayan Arc, Central Asia and southern India. Most families were found to be significantly more vulnerable to climate change than expected by chance. Our findings build on previous work on reptile extinction risk to provide an overview of the risk posed to reptiles by climate change. Despite significant data gaps for a number of traits, we recommend that these findings are integrated into reassessments of species' extinction risk, to monitor both immediate and slow-acting threats to reptiles. Highlights: The first ever global trait-based analysis of climate change vulnerability in reptiles Data were collected for a random sample of 1498 reptiles. 80.5% of species were highly sensitive to climate change. Overall, 22% of species were found to be highly vulnerable to climate change. Climate change vulnerable species do not spatially overlap species listed as threatened on the IUCN Red List.